Paradigmatic versus Historical Thinking: The Case of Rabbinic Judaism - Neusner, Jacob (History and theory, 1997)
The idea of history, with its rigid distinction between past and present and its careful sifting of connections from the one to the other, came quite late onto the scene of intellectual life. Both Judaism and Christianity for most of their histories have read the Hebrew Scriptures from within an other-than-historical framework. They found in Scripture's words paradigms of an enduring present, by which all things must take their measure; they possessed no conception whatsoever of the pastness of the past. Rabbinic Judaism invented an entirely new way to think about times past and to keep all time—past, present, and future—within a single framework. For that purpose, a model was constructed, consisting of selected events held to form a pattern that imposes order and meaning on the chaos of what happens, whether past or present or future. Time measured in the paradigmatic manner is time formulated by a free-standing, (incidentally) atemporal model, not appealing to the course of sun and moon, nor concerned with the metaphor of human life and its cyclicality. Not only so, but the paradigm obliterates distinctions between past, present, and future, between here and now and then and there. The past participates in the present, the present recapitulates the past, and the future finds itself determined, predetermined really, within the same free-standing structure comprised by God's way of telling time.